Cellulose composite waterproof flame retardant and preparation method thereof

By modifying the flame retardant composite of calcium borate and carbon nanotubes, the problem of waterproof flame retardant reducing the mechanical strength of the paper is solved, and efficient flame retardant and waterproof performance is achieved, while improving the tensile strength of the paper.

CN120443508AActive Publication Date: 2025-08-08ZHEJIANG NANYUAN NEW MATERIAL TECH CO LTD
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202510933871.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-08
Publication Date
2025-08-08
Estimated Expiration
2045-07-08

AI Technical Summary

Technical Problem

While the existing waterproof flame retardants improve the waterproof performance of paper, the encapsulated walls destroy the cross-linked grid of cellulose fibers, resulting in a decrease in the mechanical strength of the paper.

Method used

A flame retardant composite of modified calcium borate and carbon nanotubes is used to form a flame retardant covering layer by grafting acrylamide monomer on the surface of calcium borate and compounding it with ammonium polyphosphate microcapsules to form a flame retardant cover layer to enhance the binding force and tensile strength of cellulose fibers.

Benefits of technology

Under high content addition, the flame retardant not only has good waterproof and flame retardant effects, but also improves the tensile strength and mechanical properties of the paper and maintains the overall performance of the paper.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120443508A_ABST
    Figure CN120443508A_ABST
Patent Text Reader

Abstract

The invention relates to the field of flame retardant preparation, in particular to a cellulose composite waterproof flame retardant and a preparation method thereof, and solves the problems that an existing waterproof flame retardant is poor in flame retardant effect when a low-content waterproof flame retardant is used, a capsule wall material in a high-content waterproof flame retardant damages cross-linked grids of paper cellulose fibers, and the flame retardant effect is poor. The preparation method comprises the following steps: preparing modified calcium borate, putting nano calcium borate into absolute ethyl alcohol for ultrasonic modification, grafting on the surface of calcium borate to obtain pre-grafted calcium borate, putting the pre-grafted calcium borate and an acrylamide monomer into an aqueous solution of ethyl alcohol, and adding an AIBN reagent for reaction to obtain a calcium borate grafted compound; and then compounding the carbon nano tube, the calcium borate grafted compound and the silanized ammonium polyphosphate microcapsule to obtain the flame retardant. According to the invention, under the condition of high-content addition, the paper has relatively high tensile strength and flame retardant property at the same time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of flame retardant preparation, and in particular to a cellulose composite waterproof flame retardant and a preparation method thereof. Background Art

[0002] Cellulose materials are widely used in paper. They are derived from wood, cotton, straw, hemp, reeds, and other materials, with a cellulose content of approximately 40% or more. However, the disadvantage of cellulose materials is that they are easily flammable, which has limited their further use and development. Therefore, research on the flame retardancy of cellulose has been carried out since the last century. From the initial impregnation and coating of inorganic substances for flame retardancy, to the current method of adding flame retardants to the cellulose pulp, combining the flame retardant components with the cellulose material before the material is formed, and then obtaining flame-retardant cellulose, it can effectively improve the flame retardancy of cellulose materials. Another disadvantage of natural cellulose is its high hygroscopicity, which absorbs moisture in humid environments. Not only does this reduce the mechanical strength of the material and make it easy to deform, but the flame retardant also reduces the bonding strength with the cellulose, allowing it to reach the surface of the cellulose material, resulting in a lack of flame retardancy and durability of the flame-retardant paper. The paper only achieves a surface flame retardant effect. For this reason, existing flame retardants are mostly coated with hydrophobic encapsulation wall materials before being combined with cellulose, thus solving the waterproofing problem.

[0003] However, it was found during use that the tensile strength of paper was significantly reduced with the use of the above-mentioned waterproof flame retardants. For example, in order to achieve the same limiting oxygen index after encapsulation of the traditional flame retardant ammonium polyphosphate APP, the amount of additive used must be doubled. The presence of non-flame retardant components by weight will reduce the effectiveness of the flame retardant, and increasing the amount of encapsulated flame retardant will lead to a decrease in paper strength. The capsule material will destroy the fiber hydrogen bond network and occupy the original fiber hydrogen bond cross-linking sites. In summary, if high-quality waterproof and flame-retardant paper is to be prepared, the amount of encapsulated flame retardant must be increased, and increasing the amount of flame retardant will reduce the mechanical strength and tensile strength of the paper. Summary of the Invention

[0004] In order to solve the problem that while the existing waterproof flame retardants have better waterproof performance after encapsulation treatment, the encapsulation wall material in the high-content waterproof flame retardant destroys the cross-linked network of paper cellulose fibers, causing the mechanical strength of the paper to decrease, the present invention provides a cellulose composite waterproof flame retardant and a preparation method thereof.

[0005] The technical solution adopted by the present invention is as follows: First, the present application provides a method for preparing a cellulose composite waterproof flame retardant, which includes the following specific preparation steps: S1. Preparation of modified calcium borate: nano calcium borate is placed in anhydrous ethanol and ultrasonically treated, then a modifying reagent is added to react, and then separated and washed to obtain modified calcium borate; S2, surface grafting of calcium borate, dispersing modified calcium borate in anhydrous toluene to form a modified calcium borate dispersion, adding a RAFT agent and a DCC catalyst to the modified calcium borate dispersion and mixing them uniformly to obtain pre-grafted calcium borate; The pre-grafted calcium borate and acrylamide monomer are placed in an ethanol aqueous solution, and an AIBN reagent is added for reaction. After the reaction is completed, post-treatment is performed to obtain a calcium borate grafted complex; S3. Preparation of flame retardant: carbon nanotubes are placed in sodium dodecylbenzene sulfonate and ultrasonically treated to form a CNT dispersion liquid, and then ammonium polyphosphate microcapsules are dispersed in an ethanol solution, and a silane coupling agent is added to react to form silanized ammonium polyphosphate microcapsules, and the calcium borate grafted complex is dispersed in deionized water, and then the silanized ammonium polyphosphate microcapsules are added, and high-speed centrifugation is performed to homogenize to obtain a homogeneous composite liquid, and the CNT dispersion liquid is slowly added dropwise to the homogeneous composite liquid and ultrasonically treated simultaneously, and then rotary evaporation is performed to obtain the flame retardant.

[0006] This application uses nano calcium borate as a flame retardant covering layer to isolate oxygen and heat, thereby protecting the underlying substrate. However, simply adding nano calcium borate cannot improve the tensile strength of the paper. On the contrary, due to the lamellar structure of nano calcium borate, the tensile strength of the paper will decrease to a certain extent. Because the lamellar structure of the material added to the paper preparation will occupy the binding sites between the fibers, and the presence of the lamellar material will make the paper a stress concentration point under the action of external force, causing cracks to form, and the lamellar material will change the pore distribution of the paper, and the stress will be concentrated on the lamellar when subjected to force. The edge of the material causes uneven force on the fiber, which makes it easy to break. Therefore, the surface of calcium borate is modified and grafted, and a polymer is used as a bridge to graft calcium borate and connect it to the fiber of the pulp. The acrylamide monomer polymer has good film-forming and adhesion properties, and is easy to form hydrogen bonds with the fiber, thereby increasing the bonding area and bonding force between the fibers. After the nano calcium borate is modified, the agglomeration of nanoparticles can be effectively prevented. The solubility and dispersibility of the polymer can be utilized by the grafted polymer, so that the nano material is more evenly dispersed in the pulp suspension and paper structure.

[0007] Secondly, the present application also adds carbon nanotubes in the process of preparing the flame retardant. The presence of carbon nanotubes improves the compressive strength of the expanded carbon layer formed at high temperature, and reduces the risk of carbon layer fracture. The carbon nanotubes extend the gas diffusion path and prevent combustible gas from passing directly through the cracks, thereby enhancing the flame retardant effect, and can quickly dissipate heat laterally to avoid local overheating that causes carbon layer fracture, thereby protecting the base material from high-temperature thermal degradation.

[0008] Preferably, the preparation steps of nano calcium borate in step S1 are as follows: Calcium chloride dihydrate is dissolved in anhydrous ethanol to form a calcium chloride solution, and then borax is placed in deionized water and stirred to form a borax solution. The borax solution is added dropwise to the calcium chloride solution and heated to react. After the reaction is completed, the precipitate is washed with deionized water and filtered to obtain nano calcium borate.

[0009] Preferably, the molar ratio of calcium chloride dihydrate to borax is 2:1, the reaction temperature is 70-80° C., and the reaction time is 6-8 hours.

[0010] Preferably, the modification reagent in step S1 is γ-aminopropyltriethoxysilane, the solid-liquid ratio of the nano-calcium borate to the modification reagent is 1-3g:10mL, the modification reaction temperature is 70-90°C, the modification reaction time is 12h, and the modification environment is a nitrogen atmosphere.

[0011] Preferably, in step S2, the mass ratio of modified calcium borate to RAFT agent and DCC catalyst is 4-6:1-3:1, the pre-grafting reaction temperature is room temperature, and the reaction time is 24 hours; The mass ratio of the pre-grafted calcium borate to the acrylamide monomer is 1:10-20, the added amount of the AIBN reagent is 1%-5% of the pre-grafted calcium borate, the grafting reaction temperature is 60-80° C., and the reaction time is 6 hours.

[0012] Preferably, the preparation steps of the ammonium polyphosphate microcapsules in step S3 are as follows: Ethyl cellulose is dissolved in ethyl acetate to form a prepolymer solution, ammonium polyphosphate and an emulsifier are added to the prepolymer solution and stirred to form a mixed solution, and then TDI is dissolved in ethyl acetate to form a TDI solution, and the TDI solution is added dropwise to the mixed solution to react to obtain ammonium polyphosphate microcapsules.

[0013] Preferably, the mass ratio of the ethyl cellulose to ammonium polyphosphate and TDI is 2-10:100:5-10, the emulsifier is dodecylphenol polyoxyethylene ether, the amount of the emulsifier added is 0.1-0.5% of the mass of ammonium polyphosphate, the reaction temperature in the mixed solution is 70-90°C, and the reaction time is 5-8h.

[0014] Preferably, in step S3, the composite mass ratio of the calcium borate grafted composite to the silylated ammonium polyphosphate microcapsules and CNTs is 25-40:20:1-5, and the concentration of the CNT dispersion is 0.5 wt %.

[0015] Preferably, the calcium borate grafted complex is dispersed in deionized water at a solid-liquid ratio of 25-40 g:500 mL, the high-speed centrifugal homogenization speed is 2000 rpm, the homogenization time is 15 min-30 min, the CNT dispersion drop rate is 1 mL / min, and the ultrasonic treatment power is 200 W.

[0016] Secondly, the present application provides a flame retardant prepared according to the preparation method of a cellulose composite waterproof flame retardant provided above. The amount of the flame retardant added to the pulp is 8-15%, and it can be used in excess without reducing the mechanical strength and tensile strength of the paper.

[0017] The beneficial effects of the present invention are: In the flame retardant of the present application, calcium borate sheet material and acrylamide monomer are combined by in-situ synthesis, thereby connecting the inorganic nanosheet material through organic long chains. Through the organic long chains, the flame retardant not only has a good flame retardant effect in paper, but also can rely on the rigidity of the long chains to enhance the tensile strength of the paper; the use of CNT can also promote the formation of a carbon layer and form a unique three-dimensional structure within the carbon layer, further enhancing the flame retardancy, and the subsequent silanization of ammonium polyphosphate can also enhance the waterproof effect of ammonium polyphosphate, extend the storage time, and have a better moisture-proof effect, and the calcium borate grafted with PAM decomposes to form a glassy substance during combustion, and its layered structure can also absorb the free radicals generated by combustion, thereby interrupting the chain reaction. In summary, the flame retardant of the present application not only has a good flame retardant effect, but also strengthens the cross-linking of the internal fibers of the paper. When used in large quantities, it can also improve or maintain the tensile strength and mechanical properties of the paper. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 Graph showing the limiting oxygen index of the examples of the present invention and the comparative examples.

[0019] Figure 2 1 is a data graph showing the tensile strength of paper according to the embodiment of the present invention and the comparative example. DETAILED DESCRIPTION

[0020] The following will refer to the attached Figure 1 To the attached Figure 2 The embodiments of the present invention are described in detail. It should be understood by those skilled in the art that these embodiments are only used to explain the technical principles of the present invention and are not intended to limit the scope of protection of the present invention.

[0021] Preparation Example 1 Preparation of Nano-Calcium Borate 0.050 mol of calcium chloride dihydrate was placed in 30 mL of anhydrous ethanol, heated to 75°C and stirred to dissolve to form a calcium chloride solution. Then 0.025 mol of borax was placed in 200 mL of deionized water and stirred to form a borax solution. The borax solution was added dropwise to the calcium chloride solution and maintained at 75°C for 7 hours. After the reaction, the precipitate was washed with deionized water and filtered to obtain nano-calcium borate.

[0022] Preparation Example 2 Preparation of Nano-Calcium Borate The difference between this preparation example and preparation example 1 is that the temperature is raised to 70°C and stirred to dissolve to form a calcium chloride solution, and the temperature is maintained at 70°C for reaction for 6 hours. The remaining steps are the same as those in preparation example 1.

[0023] Preparation Example 3 Preparation of Nano-Calcium Borate The difference between this preparation example and preparation example 1 is that the temperature is raised to 80°C and stirred to dissolve to form a calcium chloride solution, and the temperature is maintained at 80°C for reaction for 8 hours. The remaining steps are the same as those in preparation example 1.

[0024] Preparation Example 4 Preparation of ammonium polyphosphate microcapsules 6 g of ethyl cellulose was dissolved in 200 mL of ethyl acetate to form a prepolymer solution. 100 g of ammonium polyphosphate and 0.3 g of emulsifier were added to the prepolymer solution and stirred to form a mixed solution. 8 g of TDI was then dissolved in 30 mL of ethyl acetate to form a TDI solution. The TDI solution was added dropwise to the mixed solution, and the temperature was raised to 80°C for reaction for 6.5 hours. After cooling, the mixture was filtered and ground to obtain ammonium polyphosphate microcapsules.

[0025] Preparation Example 5 Preparation of ammonium polyphosphate microcapsules 2 g of ethyl cellulose was dissolved in 200 mL of ethyl acetate to form a prepolymer solution. 100 g of ammonium polyphosphate and 0.1 g of emulsifier were added to the prepolymer solution and stirred to form a mixed solution. 5 g of TDI was then dissolved in 30 mL of ethyl acetate to form a TDI solution. The TDI solution was added dropwise to the mixed solution, and the temperature was raised to 70 ° C for reaction for 5 h. After cooling, the mixture was filtered and ground to obtain ammonium polyphosphate microcapsules.

[0026] Preparation Example 6 Preparation of ammonium polyphosphate microcapsules 10 g of ethyl cellulose was dissolved in 200 mL of ethyl acetate to form a prepolymer solution. 100 g of ammonium polyphosphate and 0.5 g of emulsifier were added to the prepolymer solution and stirred to form a mixed solution. Then 10 g of TDI was dissolved in 30 mL of ethyl acetate to form a TDI solution. The TDI solution was added dropwise to the mixed solution, and the temperature was raised to 90 ° C for reaction for 8 hours. After cooling, the mixture was filtered and ground to obtain ammonium polyphosphate microcapsules.

[0027] Example 1

[0028] Preparation of Cellulose Composite Waterproof Flame Retardant S1. The nano-calcium borate prepared in Preparation Example 1 was placed in anhydrous ethanol at a solid-liquid ratio of 1 g:100 mL and ultrasonically treated for 30 min. Then, γ-aminopropyltriethoxysilane was added to the nano-calcium borate at a solid-liquid ratio of 2 g:10 mL. The mixture was refluxed at 80° C. in a nitrogen environment for 12 h, and then centrifuged. The mixture was washed with ethanol and then vacuum-dried to obtain modified calcium borate. S2. Dispersing the modified calcium borate in anhydrous toluene at a solid-liquid ratio of 1 g:100 mL to form a modified calcium borate dispersion, adding a RAFT agent and a DCC catalyst to the modified calcium borate dispersion and mixing them evenly, wherein the mass ratio of the modified calcium borate to the RAFT agent and the DCC catalyst is 5:2:1, reacting at room temperature for 24 h, centrifuging and filtering the precipitate, washing it alternately with toluene and ethanol, and drying it to obtain pre-grafted calcium borate; Pre-grafted calcium borate and acrylamide monomer were placed in an ethanol aqueous solution (water:ethanol = 1:1) at a solid-liquid ratio of 1 g:15 g:130 mL, and AIBN reagent was added for reaction. The amount of AIBN reagent added was 3% of the pre-grafted calcium borate. The reaction was heated to 70°C for 6 h, followed by dialysis with a MWCO of 10 kDa to remove free PAM. The calcium borate grafted complex was obtained after freeze-drying. S3. Preparation of flame retardant: carbon nanotubes were placed in 1wt% sodium dodecylbenzene sulfonate at a solid-liquid ratio of 1g:200mL and ultrasonically treated for 1h. The ultrasonic treatment power was 500W and the frequency was 20kHz to form a CNT dispersion. The concentration of the CNT dispersion was 0.5wt%. Then, the ammonium polyphosphate microcapsules prepared in Preparation Example 4 were dispersed in an ethanol solution at a solid-liquid ratio of 1g:5mL. Then, a silane coupling agent γ-methacryloxypropyltrimethoxysilane was added to react. The amount of γ-methacryloxypropyltrimethoxysilane added was 0.5wt% of the ammonium polyphosphate microcapsules. The method comprises the following steps: preparing a silylated ammonium polyphosphate microcapsule comprising 20% by mass of the silylated ammonium polyphosphate microcapsules, dispersing the calcium borate grafted composite in deionized water at a solid-liquid ratio of 30 g:500 mL, adding the silylated ammonium polyphosphate microcapsules, and adding the calcium borate grafted composite to the silylated ammonium polyphosphate microcapsules to form CNT microcapsules in a mass ratio of 30:20:3. The mixture is homogenized at a centrifugal speed of 2000 rpm for 20 min to obtain a homogeneous composite liquid. The CNT dispersion is added dropwise to the homogeneous composite liquid at a speed of 1 mL / min and simultaneously ultrasonicated at a power of 200 W. After completion, the mixture is rotary evaporated to obtain a flame retardant.

[0029] Example 2

[0030] Preparation of Cellulose Composite Waterproof Flame Retardant S1. The nano-calcium borate prepared in Preparation Example 2 was placed in anhydrous ethanol at a solid-liquid ratio of 1 g: 100 mL and ultrasonically treated for 30 min. Then, γ-aminopropyltriethoxysilane was added to the nano-calcium borate at a solid-liquid ratio of 1 g: 10 mL. The mixture was refluxed at 70° C. in a nitrogen environment for 12 h, and then centrifuged. The mixture was washed with ethanol and then vacuum-dried to obtain modified calcium borate. S2. Dispersing the modified calcium borate in anhydrous toluene at a solid-liquid ratio of 1 g:100 mL to form a modified calcium borate dispersion, adding a RAFT agent and a DCC catalyst to the modified calcium borate dispersion and mixing them evenly, wherein the mass ratio of the modified calcium borate to the RAFT agent and the DCC catalyst is 4:1:1, reacting at room temperature for 24 h, centrifuging and filtering the precipitate, washing it alternately with toluene and ethanol, and drying it to obtain pre-grafted calcium borate; Pre-grafted calcium borate and acrylamide monomer were placed in an ethanol aqueous solution (water:ethanol = 1:1) at a solid-liquid ratio of 1 g:10 g:130 mL, and AIBN reagent was added for reaction. The amount of AIBN reagent added was 1% of the pre-grafted calcium borate. The reaction was heated to 60°C for 6 hours, followed by dialysis with a MWCO of 10 kDa to remove free PAM. The calcium borate grafted complex was obtained after freeze-drying. S3. Preparation of flame retardant: carbon nanotubes were placed in 1wt% sodium dodecylbenzene sulfonate at a solid-liquid ratio of 1g:200mL and ultrasonically treated for 1h. The ultrasonic treatment power was 500W and the frequency was 20kHz to form a CNT dispersion. The concentration of the CNT dispersion was 0.5wt%. Then, the ammonium polyphosphate microcapsules prepared in Preparation Example 5 were dispersed in an ethanol solution at a solid-liquid ratio of 1g:5mL. Then, a silane coupling agent γ-methacryloxypropyltrimethoxysilane was added to react. The amount of γ-methacryloxypropyltrimethoxysilane added was 0.5wt% of the ammonium polyphosphate microcapsules. The mass ratio of the calcium borate grafted composite to the silanized ammonium polyphosphate microcapsules is 20% to form silanized ammonium polyphosphate microcapsules, the calcium borate grafted composite is dispersed in deionized water at a solid-liquid ratio of 25 g: 500 mL, and the silanized ammonium polyphosphate microcapsules are added, and the composite mass ratio of the calcium borate grafted composite to the silanized ammonium polyphosphate microcapsules and CNTs is 25:20:1. The mixture is homogenized at a centrifugal speed of 2000 rpm for 15 min to obtain a homogeneous composite liquid. The CNT dispersion is added dropwise to the homogeneous composite liquid at a speed of 1 mL / min and simultaneously ultrasonicated at a power of 200 W. After completion, rotary evaporation is performed to obtain a flame retardant.

[0031] Example 3

[0032] Preparation of Cellulose Composite Waterproof Flame Retardant S1. The nano-calcium borate prepared in Preparation Example 3 was placed in anhydrous ethanol at a solid-liquid ratio of 1 g:100 mL and ultrasonically treated for 30 min. Then, γ-aminopropyltriethoxysilane was added to the nano-calcium borate at a solid-liquid ratio of 3 g:10 mL. The mixture was refluxed at 90° C. in a nitrogen environment for 12 h, and then centrifuged. The mixture was washed with ethanol and then vacuum-dried to obtain modified calcium borate. S2. Dispersing the modified calcium borate in anhydrous toluene at a solid-liquid ratio of 1 g:100 mL to form a modified calcium borate dispersion, adding a RAFT agent and a DCC catalyst to the modified calcium borate dispersion and mixing them evenly, wherein the mass ratio of the modified calcium borate to the RAFT agent and the DCC catalyst is 6:3:1, reacting at room temperature for 24 h, centrifuging and filtering the precipitate, washing it alternately with toluene and ethanol, and drying it to obtain pre-grafted calcium borate; Pre-grafted calcium borate and acrylamide monomer were placed in an ethanol aqueous solution (water:ethanol = 1:1) at a solid-liquid ratio of 1 g:20 g:130 mL. AIBN reagent was added to react at a concentration of 5% of the pre-grafted calcium borate. The mixture was heated to 80°C for 6 h and then dialyzed against a MWCO of 10 kDa to remove free PAM. The resulting mixture was freeze-dried to obtain a calcium borate grafted complex. S3. Preparation of flame retardant: carbon nanotubes were placed in 1wt% sodium dodecylbenzene sulfonate at a solid-liquid ratio of 1g:200mL and ultrasonically treated for 1h. The ultrasonic treatment power was 500W and the frequency was 20kHz to form a CNT dispersion. The concentration of the CNT dispersion was 0.5wt%. Then, the ammonium polyphosphate microcapsules prepared in Preparation Example 6 were dispersed in an ethanol solution at a solid-liquid ratio of 1g:5mL. Then, a silane coupling agent γ-methacryloxypropyltrimethoxysilane was added to react. The amount of γ-methacryloxypropyltrimethoxysilane added was 0.5wt% of the ammonium polyphosphate microcapsules. The method comprises the following steps: preparing a silanized ammonium polyphosphate microcapsule comprising 20% by mass of the composite material, forming silanized ammonium polyphosphate microcapsules, dispersing the calcium borate grafted composite in deionized water at a solid-liquid ratio of 40 g:500 mL, adding the silanized ammonium polyphosphate microcapsules, and adding the calcium borate grafted composite to the silanized ammonium polyphosphate microcapsules to form a silanized ammonium polyphosphate microcapsule. The composite material is a composite material of 40:20:5 by mass ratio, and homogenizing the composite material at a centrifugal speed of 2000 rpm for 30 min to obtain a homogeneous composite liquid. The CNT dispersion is added dropwise to the homogeneous composite liquid at a speed of 1 mL / min and simultaneously ultrasonicated at a power of 200 W. After completion, rotary evaporation is performed to obtain a flame retardant.

[0033] Comparative Example 1 - No Nano Calcium Borate Used Preparation of Cellulose Composite Waterproof Flame Retardant S1. Silica was dispersed in anhydrous toluene at a solid-liquid ratio of 1 g:100 mL to form a silica dispersion. A RAFT agent and a DCC catalyst were added to the silica dispersion and mixed evenly. The mass ratio of silica to the RAFT agent and the DCC catalyst was 5:2:1. The mixture was reacted at room temperature for 24 h. The precipitate was centrifuged and washed alternately with toluene and ethanol, and dried to obtain pre-grafted silica. Pre-grafted silica and acrylamide monomer were placed in an ethanol aqueous solution (water:ethanol = 1:1) at a solid-liquid ratio of 1 g:15 g:130 mL, and AIBN reagent was added for reaction. The amount of AIBN reagent added was 3% of the pre-grafted silica. The reaction was heated to 70°C for 6 h, followed by dialysis with a MWCO of 10 kDa to remove free PAM. The silica-grafted composite was then freeze-dried to obtain the composite. S3. Preparation of flame retardant: carbon nanotubes were placed in 1wt% sodium dodecylbenzene sulfonate at a solid-liquid ratio of 1g:200mL and ultrasonically treated for 1h. The ultrasonic treatment power was 500W and the frequency was 20kHz to form a CNT dispersion. The concentration of the CNT dispersion was 0.5wt%. Then, the ammonium polyphosphate microcapsules prepared in Preparation Example 4 were dispersed in an ethanol solution at a solid-liquid ratio of 1g:5mL. Then, a silane coupling agent γ-methacryloxypropyltrimethoxysilane was added to react. The amount of γ-methacryloxypropyltrimethoxysilane added was 0.5wt% of the ammonium polyphosphate microcapsules. The silica grafted composite was dispersed in deionized water at a solid-liquid ratio of 30 g:500 mL, and the silanized ammonium polyphosphate microcapsules were added. The composite mass ratio of the silica grafted composite, the silanized ammonium polyphosphate microcapsules and the CNTs was 30:20:3. The mixture was homogenized at a centrifugal speed of 2000 rpm for 20 min to obtain a homogeneous composite liquid. The CNT dispersion was dropwise added to the homogeneous composite liquid at a speed of 1 mL / min and simultaneously ultrasonicated at a power of 200 W. After the end, the mixture was rotary evaporated to obtain a flame retardant.

[0034] Comparative Example 2: Direct addition of PAM long chain in flame retardant Preparation of Cellulose Composite Waterproof Flame Retardant S1. Mixing the nano-calcium borate prepared in Preparation Example 1 with polyacrylamide at a weight ratio of 1:12, and grinding to form a mixed powder; S2. Preparation of flame retardant: carbon nanotubes were placed in 1wt% sodium dodecylbenzene sulfonate at a solid-liquid ratio of 1g:200mL and ultrasonically treated for 1h. The ultrasonic treatment power was 500W and the frequency was 20kHz to form a CNT dispersion. The concentration of the CNT dispersion was 0.5wt%. Then, the ammonium polyphosphate microcapsules prepared in Preparation Example 4 were dispersed in an ethanol solution at a solid-liquid ratio of 1g:5mL. Then, a silane coupling agent γ-methacryloxypropyltrimethoxysilane was added to react. The amount of γ-methacryloxypropyltrimethoxysilane added was 0.5wt% for ammonium polyphosphate microcapsules. The mixed powder in step S1 is dispersed in deionized water at a solid-liquid ratio of 30 g: 500 mL, and the silanized ammonium polyphosphate microcapsules are added. The composite mass ratio of the mixed powder, the silanized ammonium polyphosphate microcapsules and the CNTs is 30:20:3. The mixture is homogenized at a centrifugal speed of 2000 rpm for 20 min to obtain a homogeneous composite liquid. The CNT dispersion is added dropwise to the homogeneous composite liquid at a speed of 1 mL / min and simultaneously ultrasonicated. The ultrasonic treatment power is 200 W. After completion, rotary evaporation is performed to obtain a flame retardant.

[0035] Comparative Example 3 - Nano-calcium borate was not grafted with acrylamide monomer Preparation of Cellulose Composite Waterproof Flame Retardant S1. The nano-calcium borate prepared in Preparation Example 1 was placed in anhydrous ethanol at a solid-liquid ratio of 1 g:100 mL and ultrasonically treated for 30 min. Then, γ-aminopropyltriethoxysilane was added to the nano-calcium borate at a solid-liquid ratio of 2 g:10 mL. The mixture was refluxed at 80° C. in a nitrogen environment for 12 h, and then centrifuged. The mixture was washed with ethanol and then vacuum-dried to obtain modified calcium borate. S2. Preparation of flame retardant: carbon nanotubes were placed in 1wt% sodium dodecylbenzene sulfonate at a solid-liquid ratio of 1g:200mL and ultrasonically treated for 1h at a power of 500W and a frequency of 20kHz to form a CNT dispersion with a concentration of 0.5wt%. Then, the ammonium polyphosphate microcapsules prepared in Preparation Example 4 were dispersed in an ethanol solution at a solid-liquid ratio of 1g:5mL, and then a silane coupling agent γ-methacryloxypropyltrimethoxysilane was added to react with ammonium polyphosphate. The amount of γ-methacryloxypropyltrimethoxysilane added was 0.5wt%. The modified calcium borate is dispersed in deionized water at a solid-liquid ratio of 30 g: 500 mL, and the silanized ammonium polyphosphate microcapsules are added. The composite mass ratio of the modified calcium borate, the silanized ammonium polyphosphate microcapsules and the CNTs is 30:20:3. The mixture is homogenized at a centrifugal speed of 2000 rpm for 20 minutes to obtain a homogeneous composite liquid. The CNT dispersion is added dropwise to the homogeneous composite liquid at a speed of 1 mL / min and simultaneously ultrasonically treated at a power of 200 W. After the end, rotary evaporation is performed to obtain a flame retardant.

[0036] Comparative Example 4 - Preparation of flame retardant without using carbon nanotubes Preparation of Cellulose Composite Waterproof Flame Retardant Step S1 and step S2 in this comparative example are the same as those in Preparation Example 1; S3. Preparation of flame retardant: The ammonium polyphosphate microcapsules prepared in Preparation Example 4 were dispersed in an ethanol solution at a solid-liquid ratio of 1 g:5 mL, and then a silane coupling agent γ-methacryloxypropyltrimethoxysilane was added for reaction. The amount of γ-methacryloxypropyltrimethoxysilane added was 20% of the mass of the ammonium polyphosphate microcapsules to form silylated ammonium polyphosphate microcapsules. The calcium borate grafted complex was dispersed in deionized water at a solid-liquid ratio of 30 g:500 mL, and then the silylated ammonium polyphosphate microcapsules were added. The composite mass ratio of the calcium borate grafted complex to the silylated ammonium polyphosphate microcapsules was 30:20. The mixture was homogenized at a centrifugal speed of 2000 rpm for 20 minutes to obtain a homogeneous composite liquid, which was then rotary evaporated to obtain a flame retardant.

[0037] Comparative Example 5 - Ammonium polyphosphate microcapsules did not react with silane coupling agent to form silanized Preparation of Cellulose Composite Waterproof Flame Retardant S3. Preparation of flame retardant: carbon nanotubes were placed in 1wt% sodium dodecylbenzene sulfonate at a solid-liquid ratio of 1g:200mL and ultrasonically treated for 1h at a power of 500W and a frequency of 20kHz to form a CNT dispersion. The concentration of the CNT dispersion was 0.5wt%. The calcium borate grafted composite was dispersed in deionized water at a solid-liquid ratio of 30g:500mL, and the ammonium polyphosphate microcapsules prepared in Preparation Example 4 were added. The composite mass ratio of the calcium borate grafted composite, the ammonium polyphosphate microcapsules and the CNTs was 30:20:3. The mixture was homogenized at a centrifugal speed of 2000rpm for 20min to obtain a homogeneous composite liquid. The CNT dispersion was dropped into the homogeneous composite liquid at a rate of 1mL / min and ultrasonically treated simultaneously at a power of 200W. After completion, rotary evaporation was performed to obtain the flame retardant.

[0038] The remaining steps are the same as those in Example 1.

[0039] Experiments and data The flame retardants prepared in the above examples and comparative examples were used to prepare flame retardant paper, and the preparation method was as follows: Dilute the pulp to 1%, adjust the pH value to 7.0, add flame retardant according to 10% of the dry pulp weight, ultrasonically disperse for 30 minutes, then add cationic polyacrylamide at 0.05% of the dry pulp weight, stir and then form the standard paper. The paper weight is about 60g / m 2 , and dried at 105℃ to obtain flame retardant paper.

[0040] The flame retardant paper was subjected to water contact angle and the following performance tests. The specific test standards are as follows: Tensile Strength: Tested according to GB / T 12914-2018, unit: kN / m. The tensile strength of the blank control (paper without flame retardant) was 1.79 kN / m.

[0041] Limiting oxygen index: The standard is tested according to the method of GB / T 2406.2-2009, unit: %.

[0042] The specific data are shown in Table 1 below:

[0043] Draw a line graph based on the limiting oxygen index and paper tensile strength in Table 1, as shown in Figure 1 and Figure 2 shown.

[0044] analyze According to the data in Table 1, the data of Examples 1-3 show that the flame retardant prepared by the present application can make the paper not only have a higher water contact angle and better waterproof effect, but also have a very high limiting oxygen index, and the tensile strength of the paper is as high as 2.86 or more, combining flame retardant effect and tensile strength.

[0045] According to the data in Table 1, the experimental data of Comparative Example 1 shows that its limiting oxygen index is extremely poor and the tensile strength is intact. The difference between Comparative Example 1 and Example 1 is that nano-calcium borate is not used. Therefore, it can be proved that the presence of nano-calcium borate can greatly improve the flame retardant effect.

[0046] According to the data in Table 1, the experimental data of Comparative Example 2 show that its water contact angle becomes smaller, and the limiting oxygen index decreases to a large extent, while the tensile strength is higher. The difference between Comparative Example 2 and Example 1 is that PAM is not chemically grafted with nano-calcium borate, but PAM is directly added. Therefore, it can be confirmed that the in-situ polymerization method can greatly increase the distribution uniformity of nano-calcium borate, thereby improving the flame retardant effect, and slightly affecting the waterproof performance.

[0047] According to the data in Table 1, the experimental data of Comparative Example 3 show that its limiting oxygen index decreases slightly, while the tensile strength decreases significantly. The difference between Comparative Example 3 and Example 1 is that the nano-calcium borate is not grafted with acrylamide monomer, and no PAM long-chain substance is added. Therefore, it can be confirmed that the presence of PAM can enhance the tensile strength of paper and will slightly affect the performance of the flame retardant component.

[0048] According to the data in Table 1, the experimental data of Comparative Example 4 shows that its limiting oxygen index has decreased slightly, while the water contact angle and the tensile strength of the paper remain unchanged. The difference between Comparative Example 4 and Example 1 is that carbon nanotubes are not used to prepare the flame retardant. Therefore, it can be confirmed that the use of carbon nanotubes can slightly increase the limiting oxygen index, thereby improving the flame retardant effect.

[0049] According to the data in Table 1, the experimental data of Comparative Example 5 show that its limiting oxygen index and paper tensile strength also decreased slightly. The difference between Comparative Example 5 and Example 1 is that the ammonium polyphosphate microcapsules did not react with the silane coupling agent to form silanization. Therefore, it can be confirmed that the silanization of the ammonium polyphosphate microcapsules can slightly improve the dispersion effect and the degree of cross-linking, thereby improving the flame retardant effect and the mechanical strength of the paper.

[0050] Thus far, the technical solutions of the present invention have been described in conjunction with the preferred embodiments shown in the accompanying drawings. However, it will be readily understood by those skilled in the art that the scope of protection of the present invention is obviously not limited to these specific embodiments. Without departing from the principles of the present invention, those skilled in the art may make equivalent changes or substitutions to the relevant technical features, and the technical solutions after such changes or substitutions will fall within the scope of protection of the present invention.

Claims

1. A method for preparing a cellulose composite waterproof flame retardant, characterized in that: The method comprises the following specific preparation steps: S1, dispersing nano calcium borate in an organic solvent, and then adding a modifying reagent to react to obtain modified calcium borate; S2, mixing modified calcium borate, a chain transfer agent, and a catalyst to obtain pre-grafted calcium borate, and then reacting the pre-grafted calcium borate, acrylamide monomer, and an AIBN reagent in an organic solvent to obtain a calcium borate grafted complex; S3. Carbon nanotubes are prepared into a CNT dispersion, and then ammonium polyphosphate microcapsules are reacted with a silane coupling agent to form silanized ammonium polyphosphate microcapsules. The calcium borate grafted complex and the silanized ammonium polyphosphate microcapsules are homogenized by high-speed centrifugation to obtain a homogeneous composite liquid. The CNT dispersion is then slowly added dropwise to the homogeneous composite liquid and simultaneously subjected to ultrasonic treatment to obtain a flame retardant.

2. The method for preparing a cellulose composite waterproof flame retardant according to claim 1, characterized in that: The preparation steps of nano calcium borate in step S1 are as follows: Calcium chloride dihydrate is dissolved in anhydrous ethanol to form a calcium chloride solution, and then borax is placed in deionized water and stirred to form a borax solution. The borax solution is added dropwise to the calcium chloride solution and heated to react. After the reaction is completed, the precipitate is washed with deionized water and filtered to obtain nano calcium borate.

3. The method for preparing a cellulose composite waterproof flame retardant according to claim 2, characterized in that: The molar ratio of calcium chloride dihydrate to borax is 2:1, the reaction temperature is 70-80°C, and the reaction time is 6-8h.

4. The method for preparing a cellulose composite waterproof flame retardant according to claim 1, characterized in that: The modification reagent in step S1 is γ-aminopropyltriethoxysilane, the solid-liquid ratio of the nano-calcium borate to the modification reagent is 1-3g:10mL, the modification reaction temperature is 70-90°C, the modification reaction time is 12h, and the modification environment is a nitrogen atmosphere.

5. The method for preparing a cellulose composite waterproof flame retardant according to claim 1, characterized in that: In step S2, the mass ratio of modified calcium borate to chain transfer agent and catalyst is 4-6:1-3:1, the reaction temperature of the mixing is room temperature, and the mixing time is 24 hours; The mass ratio of the pre-grafted calcium borate to the acrylamide monomer is 1:10-20, the added amount of the AIBN reagent is 1%-5% of the pre-grafted calcium borate, the grafting reaction temperature is 60-80° C., and the reaction time is 6 hours.

6. The method for preparing a cellulose composite waterproof flame retardant according to claim 1, characterized in that: The preparation steps of the ammonium polyphosphate microcapsules in step S3 are as follows: Ethyl cellulose is dissolved in ethyl acetate to form a prepolymer solution, ammonium polyphosphate and an emulsifier are added to the prepolymer solution and stirred to form a mixed solution, and then TDI is dissolved in ethyl acetate to form a TDI solution, and the TDI solution is added dropwise to the mixed solution to react to obtain ammonium polyphosphate microcapsules.

7. The method for preparing a cellulose composite waterproof flame retardant according to claim 6, characterized in that: The mass ratio of the ethyl cellulose to ammonium polyphosphate to TDI is 2-10:100:5-10, the emulsifier is dodecylphenol polyoxyethylene ether, and the added amount of the emulsifier is 0.1-0.5% of the mass of the ammonium polyphosphate. The reaction temperature in the mixed solution is 70-90° C., and the reaction time is 5-8 hours.

8. The method for preparing a cellulose composite waterproof flame retardant according to claim 1, characterized in that: In step S3, the composite mass ratio of the calcium borate grafted composite to the silanized ammonium polyphosphate microcapsules and the CNTs is 25-40:20:1-5.

9. The method for preparing a cellulose composite waterproof flame retardant according to claim 1, characterized in that: The calcium borate grafted composite is dispersed in the solvent at a solid-liquid ratio of 25-40 g:500 mL.

10. The flame retardant prepared by the method for preparing a cellulose composite waterproof flame retardant according to any one of claims 1 to 9, characterized in that: The flame retardant is added in an amount of 8-15% in the pulp.

Citation Information

Patent Citations

  • Fire retardant, ultrahigh molecular weight polyethylene fire-retardant composite material using same and preparation method thereof

    CN103694498A

  • Preparation method of flame retardant paper

    CN107059476A

  • Preparation method of high-transparency efficient flame-retardant nano-fibrillated cellulose

    CN111662392A

  • Double-shell composite nitrogen-phosphorus microcapsule flame-retardant kraft paper and preparation method thereof

    CN115491928A

  • Preparation method of ammonium polyphosphate modified water-based boron phenolic resin and flame-retardant cellulose insulation paper

    CN115926370A